STRATEGI PEMASARAN PRODUK WISATA PADA PD. KAMPAR ANEKA KARYA STANUM BANGKINANG KOTA (Jurnal Riset Manajemen Indonesia, 2020)
This study aims to determine the strategy that should be carried out by PD. Kampar Aneka Karya Stanum Bangkinang City in marketing of tour. The type of data used is primary data obtained through PD. Kampar Aneka Karya Stanum Bangkinang City and secondary data in the form of documents, files and notes that have been published. Data collection techniques are interviews, FGD (Focus Group Discussion) and research files. Data analysis was carried out using SWOT analysis, which is mapping with strength maps, strengths, weaknesses, opportunities and threats to determine the factors of effective strategy advantage. The results showed that the map of the strength of the tour marketing strategy is not new to PD. Kampar Aneka Karya Stanum Bangkinang City is in quadrant I as a market leader, namely a strategy to support aggressive growth (growth oriented strategy).